Dating kerosene releases - Scally, Kenneth (2013)
Kerosene is a common fuel for domestic heating systems. Dating petroleum spill contamination is of considerable International Interest. An accurate determination of the age of spills is needed to inform the process of assigning legal and financial responsibility. The pollution of sons and groundwater by kerosene spills is of major concern to householders and their insurers as well as regulators. Released kerosene may persist in the soil as a source of hazardous hydrocarbons for a long time, but not as long as diesel, because of the low solubility and the moderate to low volatility of kerosene constituents. Generally, hydrocarbons in kerosene biodegrade significantly under aerobic conditions provided that sufficient amounts of essential nutrients are present. Extractable petroleum hydrocarbon (EPH) analyses by Jones Environmental laboratories Ltd of soil polluted following kerosene spills were used to develop an empirical model which considered biotic and abiotic factors found at spill sites to determine the time since the kerosene spill.